2017
DOI: 10.1177/0260106017720350
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training performed at ventilatory threshold improves liver enzymes and lipid profile related to non-alcoholic fatty liver disease in adolescents with obesity

Abstract: Both high and low-intensity training improved biomarkers related to NAFLD. Thus, high-intensity training can be a safe and effective alternative to prevent and treat NAFLD in adolescents with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Of the 1495 articles screened after duplicates were removed, 55 met our inclusion criteria (eTable 1 in Supplement 1). Figure 1 illustrates the identification, screening, and inclusion process. The Cohen κ statistic for interrater reliability was 0.84 (95% CI, 0.72 to 0.96).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1495 articles screened after duplicates were removed, 55 met our inclusion criteria (eTable 1 in Supplement 1). Figure 1 illustrates the identification, screening, and inclusion process. The Cohen κ statistic for interrater reliability was 0.84 (95% CI, 0.72 to 0.96).…”
Section: Resultsmentioning
confidence: 99%
“…Some NAFLD markers improved in both intervention groups (high-density lipoprotein, ALT, AST), but there was no change in glucose, insulin, and insulin resistance. Hepatic fat has not been assessed [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…These commonly reported barriers consequently result in poor treatment adherence, low retention rates [ 5 ], and poor long-term success rates. Our prior research examining the impact of inpatient behavioral interventions on health-related outcomes among adolescents with obesity found high dropout rates ranging from 45% to 55% [ 6 , 7 , 8 , 9 , 10 , 11 ]. Other studies have found that outpatient interventions may increase program adherence [ 12 , 13 , 14 , 15 ].…”
Section: Introduction: Time For a Change?mentioning
confidence: 99%
“…Behavioral lifestyle-based interventions are the gold standard of adolescent obesity treatment [ 21 ]. In fact, we previously demonstrated that several types of in-person lifestyle interventions aiming to improve eating behavior, mental health, and physical activity levels were equally effective for inducing short-term benefits in several health-related outcomes, including quality of life in adolescents with obesity [ 6 , 7 , 8 , 9 , 10 , 11 , 22 , 23 ]. Unfortunately, the magnitude of the effects on these key outcomes was small, and the interventions appear ineffective in the long-term.…”
Section: Introduction: Time For a Change?mentioning
confidence: 99%